Formation Process of Expectations and Satisfaction of Construction Design and Build Service in Surakarta, Indonesia: The Perspective of Construction Service Users - Mar’i Muhammad, Mirza; Soepatini, Soepatini; Isa, Muzakar (International Journal of Management Science and Information Technology, 2024)
The rapid development of infrastructure in Surakarta has triggered high demand in the construction industry. Ongoing urbanization and rapid population growth are key drivers, creating the need for housing projects, public facilities, and improvements in transportation infrastructure. Despite the rapid economic growth and infrastructure development in Indonesia, particularly in Surakarta, significant progress has been made in the construction sector. However, increased demand has also brought about intense competition, especially in Design and Build projects. This research specifically aims to understand the processes related to the formation of expectations and customer satisfaction in Design and Build construction projects in Surakarta. The research methodology employed is qualitative with a descriptive approach, and data is obtained through observation, interviews, and documentation. Data sources include relevant parties involved in the use of Design and Build construction services in Surakarta, Indonesia. Descriptive data analysis is used to present the data in a descriptive manner. The findings of this research indicate that the pre-purchase stage in construction services involves needs identification, information search, and alternative evaluation. Risk analysis, especially in functional, financial, temporal, physical, psychological, social, and sensory dimensions, is crucial in the decision-making process for potential users of construction services. Preferences for service dimensions such as tangibles, reliability, responsiveness, assurance, and empathy also significantly influence the selection of service providers. The ability of construction service providers to identify and manage risks, including the principles of 'The Flower of Service, also affects customer satisfaction.